Simvastatin improves spinal fusion in rats - Bostan, Bora; Gunes, Taner; AŞCI, MURAT; Sen, Cengiz; Kelestemur, Mehmet Halidun; Erdem, Mehmet; KÖSEOĞLU, REŞİT DOĞAN; Erkorkmaz, Unal (My University, 2011)
Objective: Statins stimulate bone formation by inducing the expression of bone morphogenetic proteins (BMP-2). The aim of our study was to investigate the effects of orally administered simvastatin on spinal fusion in rats.